Design and simulation of 20MW photovoltaic power plant using PVSyst - Ashish Grover; Anita Khosla; Dheeraj Joshi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This   paper deeply explains the analysis through simulation and sizing of grid connected photovoltaic plant of 20MW for the site Devdurga, Karnataka India with use of PV syst software tool. Primarily, the trajectories the behavior of grid tied photovoltaic system at a particular location. It gives results for the geographical position taken by maps for avoiding the oversizing or under sizing of the systems which projects the installation with very much realistic conditions. The projected area is of about 110 acres would generate 44854 MWh/year for a 20MW PV system, with a performance ratio of 76.28%.Loss fraction taken for simulation and sizing is 2%.The paper also includes the study and behavior of the system   with tilt and orientation of the PV Panel which gives better simulation results at similar latitudes for any feasible sizing.